Studi Kandungan Logam Berat Pb Di Saluran Kenjeran Dan Kerang Di Muara Saluran - Rijali Noor (INFO-TEKNIK, 2003)
Kenjeran river is one of the rivers with have estuary to the kenjeran beach which have length a bout 4 km. this river was estimate that has  contaminate by high heavy metal like (Pb). It’s  can effected the contents of heavy metal in the estuary cockle. The research goals is to analysis is there any differentiate the content of heavy metal in the river, analysis the content of heavy metal in the cockle, the water’s quality and the sediment. From the research result showed there is differentiate between the content of heavy metal in the upper course to the estuary. In the upper course, the cockle and the sediment are contaminate by Pb. There are positive interaction between the contents  of Pb in the estuary. The relationship between the content of heavy metal (Pb) in the cockle, the water quality, the sediment and time in the estuary implied as the equation  :Y=1,72-0.24X1+0,0206X2 – 1,23 D1 – 0.289D2.  The goal of management strategy is to increase the environmental quality and to control the pollution with applying the planning concept, management program and monitoring.